2020
DOI: 10.1021/acscatal.0c01809
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step Replacement of an Unreactive C–H Bond by a C–S Bond Using Polysulfide as the Direct Sulfur Source in the Anaerobic Ergothioneine Biosynthesis

Abstract: Ergothioneine, a natural longevity vitamin and antioxidant, is a thiol-histidine derivative. Recently, two types of biosynthetic pathways were reported. In the aerobic ergothioneine biosyntheses, non-heme iron enzymes incorporate a sulfoxide into an sp 2 C−H bond from trimethyl-histidine (hercynine) through oxidation reactions. In contrast, in the anaerobic ergothioneine biosynthetic pathway in a green-sulfur bacterium, Chlorobium limicola, a rhodanese domain containing protein (EanB), directly replaces this u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 93 publications
3
44
0
Order By: Relevance
“…Upon further analysis we realized that soluble polysulfides generated from partially oxidized hydrogen disulfide can also serve as the primary sulfur donor [16b, 19] . This finding has been confirmed recently by an independent study [20] …”
Section: Figuresupporting
confidence: 72%
See 1 more Smart Citation
“…Upon further analysis we realized that soluble polysulfides generated from partially oxidized hydrogen disulfide can also serve as the primary sulfur donor [16b, 19] . This finding has been confirmed recently by an independent study [20] …”
Section: Figuresupporting
confidence: 72%
“…[16b, 19] This finding has been confirmed recently by an independent study. [20] Measuring the rates of ergothioneine production at concentrations of Na 2 S ranging from 1 to 50 mM showed that the enzyme reaches saturation at 5 mM (entries 2-6, Table 1). At this concentration EanB catalyzes TMH sulfurization at a rate of 1 min À1 , which is twofold faster that previously determined as maximal velocity under single turnover conditions (entry 1).…”
mentioning
confidence: 99%
“…5,17–19 One ovothiol biosynthetic pathway has also been biochemically characterized (Scheme 1). 9,10 In these pathways, the key step is the activation of imidazole sp 2 C–H bonds and replacing them with a C–S bond (catalyzed by EgtB, 12 Egt1, 14 EanB, 17,18 and OvoA, 9,20 Scheme 1). In the aerobic ergothioneine biosynthetic pathways from Mycobacterium smegmatis and Neurospora crassa , a non-heme iron enzyme (EgtB 12 or Egt1 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, one anaerobic and two aerobic 12,14,15 ergothioneine biosynthetic pathways have been discovered (Scheme 1). 5,[17][18][19] One ovothiol biosynthetic pathway has also been biochemically characterized (Scheme 1). 9,10 In these pathways, the key step is the activation of imidazole sp 2 C-H bonds and replacing them with a C-S bond (catalyzed by EgtB, 12 Egt1, 14 EanB, 17,18 and OvoA, 9,20 Scheme 1).…”
Section: Analysis Of Ovoa Homologs From Thermophilic/mesophilic Organ...mentioning
confidence: 99%
“…On the other hand, the first appearance of oxygen in the primordial atmosphere could have represented a selective pressure for the evolution of oxygen-dependent sulfoxidation. Interestingly, an alternative anaerobic pathway for the biosynthesis of the ergothioneine has been previously described in the green-sulfur bacterium, Chlorobium limicola ( Leisinger et al 2019 ), in which a rhodanese domain containing protein participate to the formation of a C − S bond, using polysulfide as the direct sulfur source ( Cheng et al 2020 ). Among the two strictly anaerobic bacteria displaying OvoA-like sequences, S. hongkongensis is involved in marine sedimentary sulfur oxidation and denitrification: it grew chemolithoautotrophically using thiosulfate, sulfide, or hydrogen as electron donor and nitrate as the electron acceptor under anoxic conditions ( Chen and Dong 2005 ).…”
Section: Discussionmentioning
confidence: 99%